HUBUNGAN PENGETAHUAN DENGAN SIKAP PENANGANAN DISMENOREA DI SMK EKONOMIKA GHAMA D'LEADER SCHOOL - Adinda Zein Nur (2020)
Reproductive health problems such as dysmenorrhoea are experienced by some female teenagers. They need to have knowledge about dysmenorrhoea to be able to apply a good attitude in dealing with the experienced dysmenorrhoea. The purpose of this study was to determine the relationship of knowledge with attitudes in dealing with dysmenorrhoea in adolescents. The design of this research was associative design with cross-sectional approach. The population in this study was class X students at the Economics Vocational School Ghama D'Leader School in Depok City who experienced dysmenorrhoea. The sampling method used was purposive sampling and obtained a sample of 61 respondents. Data were analyzed using the chi-square test and p = 0.008 (α = 0.05) was obtained. It was concluded that there was a significant relationship between knowledge and attitude in dealing with dysmenorrhoea in class X students at the Economics Vocational School Ghama D'Leader School in Depok. Good knowledge can encourage positive attitudes of adolescents to overcome the problem of dysmenorrhoea. The researcher recommends a quasi-experimental design for further research, by providing health education interventions and evaluating the effectiveness of the interventions provided.